Use Of Digital Media In Developing Umrah Packages At PT Tisaga Multazam Utama Tour Bengkulu - Anggriani Soleha; Syofian Syofian; Arifah Hidayati (Utan Kayu Publishing, 2024)
In this era of ever-growing globalization, it cannot be avoided that the development of Information Technology is experiencing rapid progress. Business people are now taking advantage of this technology to promote and market their products so that they are better known in society. The digital era has made it easier for people to get information, communicate, and even carry out transactions. This change in behavior also affects company marketing strategies, which are now increasingly shifting towards digital marketing. The use of digital media has become a solution for companies in marketing and promoting their products. PT. Tisaga Multazam Utama Tour in Bengkulu uses various digital media platforms such as Facebook, Instagram, WhatsApp and TikTok. Through this media, companies can effectively convey information about various promotional packages, including prices and types of packages offered. The presence of social media makes it easier for prospective pilgrims to obtain information about Umrah travel packages provided by companies. This research uses a descriptive approach that describes phenomena with data that is accurate and arranged systematically. Based on the interview results, it can be seen that the majority of Umrah pilgrims access social media, with 69 people following, while only 13 people do not follow. The research results also show that the digital media platform is most widely used by pilgrims to find out about PT Umrah packages. Tisaga Multazam Utama Tour is Facebook and WhatsApp, with a total of 28 respondents. SWOT analysis is carried out to identify the company's internal factors (strengths and weaknesses) and external factors (opportunities and threats). The results of the analysis show that the company's internal strengths are more dominant than weaknesses, and from the external side, opportunities are more significant than threats. This shows that the company has strengths that can be utilized to optimize the opportunities around it.